Bringing Grammar in 21st Century Classroom through Problem-Based Learning - Nurwinda Laili Puspitasari (Jurnal Sinestesia, 2023)
The urgency of adopting 21st Century Classrooms for EFL learners is affecting the notion’s teaching-learning process. One of the most important things to be studied in language is grammar. By knowing the grammar, the speakers of the language will perform the language in the perfect form. Yet, grammar is one of the hardest parts of learning a language because there are a lot of rules regarding the sentences’ structures. The teachers should be able to bring a good atmosphere of learning grammar. In this paper, the researcher tried to conclude how the 21st Century Classroom brings grammar to the English classroom. The researcher used document analysis for this study by reviewing 6 journals that related to 21st-century learning, grammar, and Problem-Based Learning (PBL). The result from the analysis showed that the typical of 21st Century Classroom helps students learn grammar better through PBL.